2010
DOI: 10.1111/j.1551-2916.2009.03531.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ultra‐Fine Hafnium Carbide Powder and its Pressureless Sintering

Abstract: Ultra‐fine HfC powders with particle sizes of 380 or 225 nm were synthesized by carbothermal reduction of HfO2 with graphite or carbon black, respectively. The investigation of the process indicated that a vacuum level as high as 5 Pa was appropriate for decreasing the reaction temperature and consequently limiting the particle growth of HfO2 reactant. Type and size distribution of carbon sources demonstrated an obvious effect on the particle size of the HfC powders obtained. A model was proposed to explain th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 15 publications
4
41
0
1
Order By: Relevance
“…(1) will provide the needed thermal energy for Eq. (2). Therefore, the heat and temperature of the whole reaction system could be effectively controlled through changing the endothermic reaction rate, which could promote the preparation of ZrC powders and inhibits the formation of by-products.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) will provide the needed thermal energy for Eq. (2). Therefore, the heat and temperature of the whole reaction system could be effectively controlled through changing the endothermic reaction rate, which could promote the preparation of ZrC powders and inhibits the formation of by-products.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…With the high-speed development of the new technology in the field of aviation and space industries, powder metallurgy and atomic energy, the advanced ultra-high temperature structure materials (such as the borides, carbides of the refractory metals zirconium, hafnium and tantalum) have attracted more and more attention due to the outstanding physical and chemical properties [1][2][3] . And zirconium carbide is one representative of these ultra-high temperature structure materials.…”
Section: Introductionmentioning
confidence: 99%
“…21 Previously, it has been reported that carbon black could limit HfO 2 growth by physically separating the oxide particles. 22 Thus, it is believed that the existence of the residual carbon in this work reduces the particle mutual contact, thus preventing the particle coarsening and leading to ultra-ne particle size.…”
Section: 20mentioning
confidence: 99%
“…However, regardless the precursors used, the carbothermal reduction reaction has to be performed at temperatures higher than 1400 1C. It is known that agglomeration and growth of oxide particles are significant at elevated temperatures [23][24][25]. Thus, the synthesized ZrC particles are usually much bigger than the precursor particles with irregular morphologies.…”
Section: Introductionmentioning
confidence: 97%